Platform Stories: The Role of Ideological Narratives in the Development of a Tourism Sharing Business Model - Mia Larson; Cecilia Cassinger (Tourism and Hospitality)
This article explores the development process of a sharing platform in the tourism industry, drawing on a longitudinal case study of a sharing-based business in adventure tourism in Sweden. The purpose is to explore how sharing business models emerge through processes of ideological narration—the strategic use of stories to shape and sustain a business. Over a two-year period, empirical data were collected through in-depth interviews, participant observations, and document study. The findings suggest that sharing business models are developed in processes of ideological narration designed to attract labour, capital, and users to a digital platform. Four master narratives are identified—sharing, sustainability, shared identity, and profit-making—narratives grounded in conflicting ideological logics. The dominance of these narratives shifts over time, reflecting different priorities and challenges encountered at various stages of a sharing business model’s development. This dynamic highlights the fluid and multi-faceted nature of narratives in shaping and sustaining sharing businesses in the tourism industry.